Fight in Hooverville - Thomas Hart Benton (artist):::Creator:::::::::::: (2024)
The fight in Hooverville from The Grapes of Wrath, v.2,p.326, edition illustrated by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate."Now you,' the deputy said to Floyd, 'you get in that car.' He reached a large hand up and took hold of Floyd's left arm. Floyd spun and swung with one movement. His fist splashed into the large face, and in the same movement he was away, dodging down the line of tents. The deputy staggered and Tom put out his foot for him to trip over. The deputy fell heavily and rolled, reaching for his gun."